1995
DOI: 10.1200/jco.1995.13.6.1470
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography studies in patients with locally advanced and/or metastatic breast cancer: a method for early therapy evaluation?

Abstract: Our data indicate that PET may be of clinical value in predicting response to chemotherapy in patients with locally advanced breast cancer and/or metastatic disease earlier than any other method used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(94 citation statements)
references
References 16 publications
2
88
0
4
Order By: Relevance
“…A decrease in tumor 18 F-FDG uptake was observed in 8 of 12 patients who had metastatic disease and who responded after the first cycle of chemotherapy (47). In another study, a rapid decrease in tumor glucose metabolism was observed after the first cycle of therapy in 6 of 9 responding patients, but there was no substantial decrease in nonresponding patients (48).…”
Section: Metabolic Response To Therapy Of Metastatic Breast Cancermentioning
confidence: 92%
“…A decrease in tumor 18 F-FDG uptake was observed in 8 of 12 patients who had metastatic disease and who responded after the first cycle of chemotherapy (47). In another study, a rapid decrease in tumor glucose metabolism was observed after the first cycle of therapy in 6 of 9 responding patients, but there was no substantial decrease in nonresponding patients (48).…”
Section: Metabolic Response To Therapy Of Metastatic Breast Cancermentioning
confidence: 92%
“…18 F-FDG PET, however, is a functional measure of tumor metabolic activity, which is potentially more sensitive in detecting change to therapy than anatomic measurements. 18 F-FDG PET has been demonstrated to be useful in the prediction of response to chemotherapy in several solid tumors, with the reduction in 18 F-FDG uptake often preceding radiological changes (4)(5)(6)(20)(21)(22). There are also emerging survival data with metabolic responses associated with a survival advantage in lung, breast, esophageal, and pancreatic cancer (5)(6)(7)21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, effective chemotherapy, when repeated, leads to diminution of glucose uptake levels to basal values while FDG uptake increases in patients receiving inefficient therapy. Reports from Nieweg et al [250], Chaiken et al [225] and Jansson et al [260] also suggest a role for PET in the follow-up of therapy.…”
Section: Breast Cancermentioning
confidence: 99%